Oviposition and Development in Gregopimpla kuwanae Viereck (Hymenoptera: Ichneumonidae), a Gregarious Ectoparasitoid Wasp Attacking the Rice Skipper Parnara guttata. (2nd March 2016) - Ueno, Takatoshi
Abstract : Gregopimpla kuwanae is a gregarious ectoparasitoid wasp attacking mature larvae and prepupae of the rice skipper Parnara guttata (Lepidoptera: Hesperiidae), a major herbivorous pest in rice paddies. Here, the biology of G. kuwanae was investigated using Galleria mellonella as a laboratory host. Adult females accepted G. mellonella cocoons for oviposition, and larvae of G. kuwanae developed successfully to adulthood on this host. Females laid, on average, 3.5 eggs per host. Time required for oviposition was relatively long (mean = 14.2 min). Survival of parasitoid offspring decreased with the increasing number of eggs on each host. Females used 18.9% of hosts for host feeding, killing the hosts with no exception. Oviposition did not occur on hosts used for feeding purpose, indicating that the parasitoid was a nonconcurrent, destructive host feeder. Newly emerging adult females carried no eggs in the ovary; females started oogenesis only after they had destructively fed on hosts. This parasitoid thus was extremely synovigenic (ovigeny index = 0). Gregopimpla kuwanae laid typically yolk-rich, anhydropic eggs. Females carried on average 15 mature eggs with 20 immature eggs, and larger females had a greater number of eggs in the ovary. Life history characteristics of G. kuwanae were discussed.